Fuzzy r-continuous and fuzzy r-semicontinuous maps - Seok Jong Lee; Eun Pyo Lee (International Journal of Mathematics and Mathematical Sciences)
We introduce a new notion of fuzzy r-interior which is an extension of Chang's fuzzy interior. Using fuzzy r-interior, we define fuzzy r-semiopen sets and fuzzy r-semicontinuous maps which are generalizations of fuzzy semiopen sets and fuzzy semicontinuous maps in Chang's fuzzy topology, respectively. Some basic properties of fuzzy r-semiopen sets and fuzzy r-semicontinuous maps are investigated.